Regent Regulation Number 61 of 2019 concerning the Civil Servant Information System within the Regional Secretariat of Gorontalo Regency - Elisia Feronika Kemur; Robin Pakudu; Umar Sako Baderan; Rifka S. Akibu (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study aims to describe the Implementation of Regent Regulation Number 61 of 2019 Concerning Civil Servant Information System in the Regional Secretariat of Gorontalo Regency. The research method uses a qualitative approach with data collection through observation, interviews and documentation. The results of the study indicate that the Implementation of Regent Regulation Number 61 of 2019 Concerning Civil Servant Information System in the Regional Secretariat of Gorontalo Regency has been implemented well, this can be seen from the communication process through socialization activities about the Civil Servant Information System which are intensively carried out and supported by quite potential human resources, namely the average education level of employees who are bachelors (S1) and have a lot of work experience as seen from the length of service of employees and have been rotated in several fields of work. In addition, the results of the researcher's observations show that there are indeed some employees who are less disciplined and do not have a good work attitude, but when compared to the total number of employees, there are still more employees who have good attitudes and discipline time than some employees who are less disciplined.